KKN-M Pemanfaatan Waktu Luang dengan Melakukan Bimbingan Belajar bagi Siswa di Desa Ndetundora 1 di Masa Pandemi Covid-19 - Emiliana Vivintha Yoman; Maimunah H Daud; Maria Waldetrudis Lidi (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2021)
Ndetundora 1 village is one of the villages in Nuabosi, precisely in Ende sub-district, in independent real work lectures (KKN), students motivate the importance of learning even during the covid 19 pandemic. The purpose of implementing this program is for students to gain learning experiences through direct involvement in the community to find problems in people's lives. In this activity, the problems encountered included a network that was difficult to access which made it difficult for students to study online during a pandemic. In addition, there were also many students who did not use their free time to study. The first step is to record students who are doing online and offline learning. The solution offered in solving problems that have been identified is to conduct learning from home (BDR) using technology media in the form of learning videos. Not only that, but another solution is to conduct tutoring in schools using a scientific approach and contextual or real media.